Perimenopausal contraception in Turkish women: A cross-sectional study - Kharbouch Sema B; Şahin Nevin H (BMC, 2007)
Abstract Background Epidemiologic research has shown that perimenopausal contraception is an important medical issue, because women during the perimenopause still need effective contraception. The objective of the study was to assess the contraceptive choices of perimenopausal Turkish women. Methods This is a descriptive cross-sectional study that in a non - random fashion recruited 202 perimenopausal and naturally menopausal women who lived in a suburban area of Istanbul. Women who took part were aged between 45-59 years old. Chief database used to identify the suitable participants in the district. Subjects who voluntarily participated in the study were interviewed in their homes by the researcher. The analysis of the data was evaluated using percentages. Results The percentage of sexually active women among the participants was 87.6%. A large majority - 80.2% - of the participants did not have any idea of when they should bring contraception to an end. The method most commonly used was withdrawal (Coitus Interruptus), represented by 38.8%. In regard to the participants' choices of medical contraception, those being utilized were the IUD (24.3%), tubal sterilization (8.9%), condom (5.9%) and COC (6.4%). Additionally, 18% of women used other traditional methods including vaginal lavage, vaginal aspirin, and even inserting a small sponge presoaked with fresh lemon juice or cola deep into the vagina. Among the perimenopausal women who participated, the IUD was the most popular and appropriate contraceptive method. Conclusion Most perimenopausal Turkish women are still using traditional methods and women's knowledge about contraception in the menopausal stages is very limited. Health professionals should provide information about perimenopausal contraception.